Pizoelectric Rectifier Development for Low Power Energy Harvesting Applications by Dual Schttky and Op-Amp - قدسية ريان (Latakia University Journal -Engineering Sciences Series, 2022)
.Piezoelectric rectifier circuit was studied and developed for low power energy harvesting applications based on dual schottky and op-amp . the types of rectifier diodes were studied and compared to obtain the diode with the best specifications for rectification with the least possible loss, so that the circuit could rectify a signal with a minimum value of 400mV. the two stage op-amp full wave rectifier was used to convert the AC signal to DC signal voltage received by piezoelectertic devices .study and simulations using the MULTISIM program to ensure obtaining a circuit capable of utilizing the piezoelectertic source signal with the least possible loss.